2009
DOI: 10.1136/bjsm.2009.059139
|View full text |Cite|
|
Sign up to set email alerts
|

The anterior cruciate ligament injury controversy: is “valgus collapse” a sex-specific mechanism?

Abstract: Background Anterior cruciate ligament (ACL) injury is a devastating injury that puts an athlete at high risk of future osteoarthritis. Identification of risk factors and development of ACL prevention programmes likely decrease injury risk. Although studies indicate that sagittal plane biomechanical factors contribute to ACL loading mechanisms, it is unlikely that non-contact ACL injuries occur solely in a sagittal plane. Some authors attempt to ascribe the solely sagittal plane injury mechanism to both female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
170
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(189 citation statements)
references
References 94 publications
(126 reference statements)
7
170
1
8
Order By: Relevance
“…While there is no obvious explanation for the discrepancy observed between these studies and our results, critical factors such as the differences in the loading conditions, sequence of sectioning the PLS and coupled motions under external tibial torque may have contributed. Numerous studies have explored the mechanics of noncontact ACL injuries in athletes to identify the precise kinematics that predispose the ACL to extreme tensile loads leading to its subsequent failure [24][25][26][27][28]. The evidence from these studies has associated excessive tibial combined valgus and external/internal rotations to be the most detrimental motion pattern to the ACL.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no obvious explanation for the discrepancy observed between these studies and our results, critical factors such as the differences in the loading conditions, sequence of sectioning the PLS and coupled motions under external tibial torque may have contributed. Numerous studies have explored the mechanics of noncontact ACL injuries in athletes to identify the precise kinematics that predispose the ACL to extreme tensile loads leading to its subsequent failure [24][25][26][27][28]. The evidence from these studies has associated excessive tibial combined valgus and external/internal rotations to be the most detrimental motion pattern to the ACL.…”
Section: Discussionmentioning
confidence: 99%
“…According to zebis et al (10) , the excessive activation of the quadriceps over the hamstrings muscles is a possible risk factor for injuries of the anterior cruciate ligament (ACL) in women. Despite the population used in this study, we believe that these mechanisms are true for men, since in vitro studies have demonstrated that the excessive activation of the quadriceps in relation to the hamstrings muscles increases the anterior shear forces of the tibia in relation to the femur and the tension in the referred ligament (11) as well as evidence suggests that this is the main injury mechanism in men (12) . Another aspect little investigated is the difference in the electrical activity in muscles of the lumbopelvic region between different landings in the male population (13) .…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism was demonstrated in a cadaver study (DeMorat, Weinhold, Blackburn, Chudik, & Garrett, 2004), but was criticized for not taking ground reaction forces into consideration. Others argue that knee abduction must be involved in the injury mechanism (Quatman & Hewett, 2009). This theory is partly based on video analyses of ACL-injured athletes where valgus or valgus collapse are frequently reported (Krosshaug et al, 2007a;Krosshaug, Slauterbeck, Engebretsen, & Bahr, 2007b;Olsen et al, 2004).…”
Section: Mechanismsmentioning
confidence: 99%